2013
DOI: 10.2139/ssrn.2285262
|View full text |Cite
|
Sign up to set email alerts
|

‘By a Silken Thread’: Regional Banking Integration and Pathways to Financial Development in Japan's Great Recession

Abstract: How do financial development and financial integration interact? We focus on Japan's Great Recession after 1990 to study this question. Regional differences in banking integration affected how the recession spread across the country: financing frictions for credit-dependent firms were more severe in less integrated prefectures, which saw larger decreases in lending by nationwide banks and lower GDP growth. We explain these cross-prefectural differences in banking integration by reference to prefectures' differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…While the domestic market integration in early modern China has been thought to be the origin of the rise of modern China (Keller and Shiue, ), Jia (forthcoming) additionally found that since the reopening of China since the 1980s, ex‐treaty port regions in China have enjoyed better performance, which indicates that the imposed treaty port system had a very long‐term positive effect on market integration and development. Meanwhile, Hoffmann and Okubo () established that local financial markets of ex‐silk‐reeling regions are less integrated with the national market and this weaker integration exacerbated ill‐functioning corporate financing in the regions during the recessionary period from the 1990s to the 2000s. That is, silk‐reeling regions successfully adjusted to the new business opportunities shown at the Yokohama market, and locally and densely interlinked corporate financing organizations were formed.…”
Section: Discussion: Long‐term Implications Of Imposed Efficiencymentioning
confidence: 99%
“…While the domestic market integration in early modern China has been thought to be the origin of the rise of modern China (Keller and Shiue, ), Jia (forthcoming) additionally found that since the reopening of China since the 1980s, ex‐treaty port regions in China have enjoyed better performance, which indicates that the imposed treaty port system had a very long‐term positive effect on market integration and development. Meanwhile, Hoffmann and Okubo () established that local financial markets of ex‐silk‐reeling regions are less integrated with the national market and this weaker integration exacerbated ill‐functioning corporate financing in the regions during the recessionary period from the 1990s to the 2000s. That is, silk‐reeling regions successfully adjusted to the new business opportunities shown at the Yokohama market, and locally and densely interlinked corporate financing organizations were formed.…”
Section: Discussion: Long‐term Implications Of Imposed Efficiencymentioning
confidence: 99%
“…This holds particularly for small and medium enterprises that are dependent on local bank credit, see Hoffmann and Okubo (2015). This may be due to a lack of good collateral, to financial regulation, or to a greater risk awareness on the side of the buyersthe notorious 'flight to quality'.…”
Section: Benign Liquidity Trapsmentioning
confidence: 99%
“…Recent research indicates that credit constraints are still relevant for Japan and its relationship banking. This holds particularly for small and medium enterprises that S. Homburg are dependent on local bank credit, see Hoffmann and Okubo (2015). As a final remark, dividing both sides by firms' revenue, the borrowing constraint could also be written as a maximum loan-to-revenue ratio, B s t =ðP t Y s t Þ B=ðP t Y s t Þ, without affecting any of the following results.…”
Section: Benign Liquidity Trapsmentioning
confidence: 99%